2023
DOI: 10.1159/000530403
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Ameliorates Podocyte Injury by Enhancing Autophagy Activity in Diabetic Kidney Disease

Abstract: Introduction: Restoration of podocyte autophagy is considered as a feasible strategy for the treatment of diabetic kidney disease (DKD). This study aimed at investigating the protective effect and potential mechanism of vitamin D on podocyte injury of DKD. Methods: Type 2 diabetic db/db mice received intraperitoneal injections of vitamin D analogue paricalcitol 400ng/kg per day for 16 weeks. Immortalized mouse podocytes were cultured in high glucose (HG) medium with active vitamin D3 calcitriol or autophagy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Recent studies have shown that vitamin D can decrease podocyte loss and inhibit podocyte hypertrophy in rodent diabetes nephropathy, 10 thus identifying podocytes as a potentially important target for the renoprotective actions of vitamin D. In some disease states, the expression of CYP24A1 is markedly elevated in kidney diseases, such as in CKD patients with acute renal inflammation, 11 despite being rendered vitamin D-deficient. Similarly to the present study, the increased expression of CYP24A1 was also observed in mice fed an HFD.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that vitamin D can decrease podocyte loss and inhibit podocyte hypertrophy in rodent diabetes nephropathy, 10 thus identifying podocytes as a potentially important target for the renoprotective actions of vitamin D. In some disease states, the expression of CYP24A1 is markedly elevated in kidney diseases, such as in CKD patients with acute renal inflammation, 11 despite being rendered vitamin D-deficient. Similarly to the present study, the increased expression of CYP24A1 was also observed in mice fed an HFD.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 1,25(OH) 2 D deficient mice developed glomerular (podocyte) injury, albuminuria, and subsequent kidney dysfunction, which were reversible upon exposure to 1,25(OH) 2 D [34]. Zhang et al also highlighted the protective effects of paricalcitol, a vitamin D analogue, in type 2 diabetic (db/db) mice, which attenuated albuminuria, podocyte injury, and mesangial matrix expansion, by improving autophagic activity [35]. Our patients with HF showed significant positive correlations between total 25(OH)D and serum albumin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency results in the respective body functions and results in various pathological consequences such as bone-softening diseases in children and in adults (Szulc et al 2023 ). Recent studies have shown a correlation between vitamin D 3 deficiency and the occurrence of respiratory infections, cardiovascular diseases, some immunological and lung disorders, and some types of cancer (Afzal et al 2021 ; Rojano-Ortega and Berral-de la Rosa 2022 ; Sîrbe et al 2022 ; Zhang et al 2023 ). The synthesis of calcitriol is compromised in patients with hepatic and/or renal problems.…”
Section: Introductionmentioning
confidence: 99%